Elevated Nrf-2 responses are insufficient to mitigate protein carbonylation in hepatospecific PTEN deletion mice - Petersen, Dennis R. (PLoS One, 2018)
OBJECTIVE: In the liver, a contributing factor in the pathogenesis of non-alcoholic fatty liver disease (NASH) is oxidative stress, which leads to the accumulation of highly reactive electrophilic α/β unsaturated aldehydes. The objective of this study was to determine the impact of NASH on protein carbonylation and antioxidant responses in a murine model. METHODS: Liver-specific phosphatase and tensin homolog (PTEN)-deletion mice (PTEN(LKO)) or control littermates were fed a standard chow diet for 45–55 weeks followed by analysis for liver injury, oxidative stress and inflammation. RESULTS: Histology and Picrosirius red-staining of collagen deposition within the extracellular matrix revealed extensive steatosis and fibrosis in the PTEN(LKO) mice but no steatosis or fibrosis in controls. Increased steatosis and fibrosis corresponded with significant increases in inflammation. PTEN-deficient livers showed significantly increased cell-specific oxidative damage, as detected by 4-hydroxy-2-nonenal (4-HNE) and acrolein staining. Elevated staining correlated with an increase in nuclear DNA repair foci (γH2A.X) and cellular proliferation index (Ki67) within zones 1 and 3, indicating oxidative damage was zonally restricted and was associated with increased DNA damage and cell proliferation. Immunoblots showed that total levels of antioxidant response proteins induced by nuclear factor erythroid-2-like-2 (Nrf2), including GSTμ, GSTπ and CBR1/3, but not HO-1, were elevated in PTEN(LKO) as compared to controls, and IHC showed this response also occurred only in zones 1 and 3. Furthermore, an analysis of autophagy markers revealed significant elevation of p62 and LC3II expression. Mass spectrometric (MS) analysis identified significantly more carbonylated proteins in whole cell extracts prepared from PTEN(LKO) mice (966) as compared to controls (809). Pathway analyses of identified proteins did not uncover specific pathways that were preferentially carbonylated in PTEN(LKO) livers but, did reveal specific strongly increased carbonylation of thioredoxin reductase and of glutathione-S-transferases (GST) M6, O1, and O2. CONCLUSIONS: Results show that disruption of PTEN resulted in steatohepatitis, fibrosis and caused hepatic induction of the Nrf2-dependent antioxidant system at least in part due to elevation of p62. This response was both cell-type and zone specific. However, these responses were insufficient to mitigate the accumulation of products of lipid peroxidation.